Stroke Recovery and Prevention Barriers Among Young African-American Men: Potential Avenues to Reduce Health Disparities. Issue 5 (September 2014) - Blixen, Carol; Perzynski, Adam; Cage, Jamie; Smyth, Kathleen; Moore, Shirley; Sila, Cathy; Pundik, Svetlana; Sajatovic, Martha
Abstract : Background: African Americans (AAs) who experience a first time stroke are younger and have double the stroke rate and more poststroke complications than other Americans.Objective: To assess perceived poststroke care barriers among younger AA men and their care partners (CPs) in order to inform the development of acceptable and effective improvements in poststroke care for this high-risk group.Methods: Ten community-dwelling AA stroke survivors and 7 of their CPs participated in focus groups and advisory board meetings. Survivors had stroke or transient ischemic attack within 1 year and a Barthel Index score >60. In focus groups, using a semi-structured interview guide, survivors and CPs identified self-perceived barriers and facilitators to poststroke care. Thematic analysis of session transcripts and the constant comparative method were used to generate themes.Results: Survivor age ranged from 34 to 64 years. Mean Barthel score was 95.5. CPs, all AA women, ranged in age from 49 to 61 years. Five CPs were wives, 1 was a fiancée, and 1 was a niece. Participants cited multiple personal, social, and societal stroke recovery challenges. Although hypertension and smoking risks were acknowledged, stress, depression, posttraumatic stress disorder, anger/frustration, personal identity change, and difficulty communicating unique needs as AA men were more frequently noted. Facilitators included family support, stress reduction, and dietary changes.Conclusions: Younger AA men and their CPs perceive multiple poststroke care barriers. Biological risk reduction education may not capture all salient aspects of health management for AA stroke survivors. Leveraging family and community strengths, addressing psychological health, and directly engaging patients with health care teams may improve care management.